Physical Activity and Fat-Related Eating Behaviour Among Patients with Cholelithiasis in Erbil City: A Case Control Study - Ali Taher Mohammed-Ameen; Yousif Mohammed Younis (Hawler Medical University, 2019)
Background and objective: The effect of physical activity and diet is an essential modifiable or environmental factor. Evidence from epidemiological studies suggests that assessing associations between diet and general health is important. The aim of the study was to assess the level of physical activity and fat-related eating behaviour of patients with cholelithiasis. Methods: A matched case-control study was done on 100 participants; 50 were patients with gallstone disease and 50 were patients without gallstone disease. The study was conducted from December 2017 to June 2018. The constructed questionnaire used and designed based on the literature review. It consisted of four parts: demographic data, physical activity, fat-related eating behaviour, and investigations. Ultrasounds were done on all study participants to confirm whether patients had gallstone disease or not. Reliability of the questionnaire was determined through a pilot study and the validity through a panel of experts from medicine and nursing fields. Frequency, percentage, mean and standard deviation, and the chi-square test was used for analyzing data. Results: In total, 70 female and 30 male patients were investigated. Most (52%) were 28 to 47 years old. Most (72%) were physically inactive. Regarding fat-related eating behaviour most (73%) had unhealthy behavior. There was a significant association between physical activity and the risk of getting cholelithiasis. Risk of disease the development was about 2.8 times higher in patients who were physically inactive (odds ratio = 2.79, 95% CI; 1.1-7.0) in comparison to patients were physically active. There was no significant difference between development of cholelithiasis and unhealthy fat-related eating behaviour (odds ratio = 0.886, 95% CI; 0.338-2.323). Conclusion: There is a significant relationship between cholelithiasis and engaging in physical activity.